Strengthening Digital Literacy and Ethical Social Media Use Among Vocational Students - Zulfi Zumala Dwi Andriani; Ahmad Faruk; Dewi Khawa; Faiqotur Rizkiyah; Muhammad Liulil Abshor; Ahmad Faiz Setiyawan (Al-Qalam Institute, 2025)
The rapid advancement of digital technology presents new challenges for Vocational High School (SMK) students, particularly concerning digital literacy and online conduct. To address this, lecturers from Prodi Tadris Bahasa Inggris (TBIG) at KH Mukhtar Syafaat University (UIMSYA) conducted a community service program aimed at enhancing SMK Al Munawwir students' understanding of digital literacy and instilling social media etiquette. Through an educational approach that included training, interactive discussions, and simulations of social media use, students gained insight into online interaction ethics, critical thinking about digital information, and wise technology utilization. The activity successfully demonstrated an increase in students' digital literacy understanding and their awareness of maintaining communication ethics on social media. This program contributes significantly to fostering a generation that is not only technologically literate but also possesses strong moral values in digital interactions.